2009
DOI: 10.1007/s10518-009-9164-z
|View full text |Cite
|
Sign up to set email alerts
|

Failure analysis of one-story precast structures for near-fault and far-fault strong ground motions

Abstract: Failure of one-story precast structures consisting of cantilever columns connected by simply supported beams was widely reported throughout the epicentral regions of the last devastating earthquakes in Turkey. As a single degree of freedom system, precast columns are designed by using the elastic spectrum given in the seismic code and by considering a seismic load reduction factor which takes into account the inelastic behavior of the columns under seismic loads. Although the existing seismic codes consider ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 10 publications
(6 reference statements)
0
15
0
Order By: Relevance
“…Some other modified versions of Park and Ang's [16] model, quite similar to the original model, have also been proposed. It is worth noting that Park and Ang model is still widely used by researchers although it was proposed in 1985 [19][20][21][22][23][24].…”
Section: Cumulative Damage Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some other modified versions of Park and Ang's [16] model, quite similar to the original model, have also been proposed. It is worth noting that Park and Ang model is still widely used by researchers although it was proposed in 1985 [19][20][21][22][23][24].…”
Section: Cumulative Damage Indicesmentioning
confidence: 99%
“…In this section, the damage index (DI) is calculated using the proposal formulation given in Eq. (24). For this purpose, eleven (11) specimens subjected to cyclic loading were carefully selected from the database compiled by M.O.…”
Section: Damage Analysis: Applicationmentioning
confidence: 99%
“…Park and Ang [3] took into account both hysteretic energy and deformation to present a damage model. Some researchers have attempted to improve this model [16][17][18], but the original ParkAng model is still widely used in structural damage analysis [19][20][21]. In order to numerically calculate damage indices, the correlation between performance levels and values of damage index has been studied [22].…”
Section: Introductionmentioning
confidence: 99%
“…Yüksel and Sürmeli [79] used the Park and Ang [4] model to evaluate the damage levels of columns with different cross-sectional dimensions and longitudinal reinforcement ratio subjected to near-fault and far-fault earthquakes. They found that, for a certain reinforcement ratio, the damage decreases as the dimensions of cross section increases.…”
Section: Effects Of Near-fault Earthquakes On Rc Structuresmentioning
confidence: 99%
“…The results of their investigation of the relationship between the probability of damage and the reinforcement ratio is shown in Table 2-2. Table 2-2 Damage probability of column Yüksel and Sürmeli [79].…”
Section: Effects Of Near-fault Earthquakes On Rc Structuresmentioning
confidence: 99%